INFLUENCE OF THE CUTTING MODE ON THE SURFACE QUALITY DURING LONGITUDINAL PLANE MILLING OF ARTICLES FROM SCOTS PINE S (Innovation in Woodworking Industry and Engineering design, 2026)
The current study investigates the changes in the surface quality of experimental samples of Scots pine (Pinus sylvestris L.) wood during a milling process, performed with different rotation speed of the cutting tool (n), feed rates (U) and different thicknesses of the removed layer (h). On the basis of the performed experiments, graphical dependencies, representing the relationship between the different factors have been derived. In order to achieve a higher quality of the milled (processed) surfaces, practical recommendations for the optimal values of the evaluated factors have been suggested. The surface roughness of the material (surface) was measured with a roughness tester, type „SurftestSJ-210“ (Mitutoyo, Japan).